The Use of Growth Factors and Mesenchymal Stem Cells in Orthopaedics: In particular, their use in Fractures and Non-Unions: A Systematic Review - L. Sinclair, Katherine; Mafi, Pouya; Mafi, Reza; s. Khan, Wasim (Current Stem Cell Research & Therapy, 2017)
Aim: The aim was to look at current evidence for treating non-unions or delayed fracture healing in regard to novel methods applying mesenchymal stem cells (MSCs) and growth factors (GF). Methods: Pre-clinical and clinical trials focusing on the use of Mesenchymal Stem Cells and Growth Factors for fracture healing were included in this review. Published articles were identified using specific search terms in Medline, Cochrane Library, PubMed, Scopus and Web of Science. Results: Of the 580 articles found, 82 met my selection criteria and were included, with 39 papers involving trials on the effects of GFs and MSCs on non-unions or bone repair. These included 11 articles on MSCs, 10 on Bone Morphogenetic Proteins, 2 on Vascular-Endothelial GF, 5 on Insulin like-GF, 4 on Transforming-GF-β, 4 on Platelet-Rich Plasma, 1 on Platelet Derived-GF and 2 on Fibroblast-GF, with the other articles included qualitatively. Overall results were positive with the addition of MSCs, Bone Morphogenetic Proteins, VEGF, IGF and TGF-β in aiding fracture healing compared to controls, with mixed results for other factors. Conclusion: Overall this review shows promising results regarding the use of MSCs and various Growth factors in the treatment of fractures and non-unions, as well as synergistic effects observed when combined together. However more research is indicated as these methods are still in the early stages of development.
Keywords: orthopaedics